Analisis Tingkat Kepuasan Masyarakat Terhadap Program Pengembangan Pendidikan dan Kreativitas Anak (Pendikresa) di Kota Samarinda - Febrianti Soleha (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Children’s education and creativity development program is carried out by the schools around the company areas embodies the company commitment related to the world of education in Samarinda. The aim of this research is to upgrade the service providers in improving the quality of services in Pendikresa Program. The sampling method used is Survey method. The data analysis methods used in this survey were descriptive analysis, customer satisfaction index and importance performance analysis. The results of the analysis illustrated that the survey on Community Satisfaction, underdone by Public Service Delivery Unit shows a figure of 71.20. It can be seen that this number fulfills the category of the value range 60% < IKM ≤ 80% which illustrates that the IKM value is in the